The Effect Of Work Quality And Supervision On The Performance Of Employees In The Ministry Of Communication And Information Service Of Lahat Regency - Bella Septiana Sukma; Rudi Eduar; Hestin Hestin (Journal of Management, Economic, and Accounting, 2026)
The purpose of this study was to determine the effect of work quality and supervision on employee performance at the Lahat Regency Communication and Information Service. The results showed that (1) work quality has a significant partial effect on employee performance, as evidenced by a significance value of 0.000 <0.05. Therefore, Ha is rejected and Ho is accepted. It can be concluded that work quality significantly influences employee performance. (2) supervision significantly influences employee performance, as evidenced by a significance value of 0.004 <0.05. Therefore, Ha is accepted and Ho is rejected. It can be concluded that supervision significantly influences employee performance. (3) work quality and supervision significantly influence employee performance at the Lahat Regency Communication and Information Service, as evidenced by a significance value of 0.000 <0.05. This means that the variables work quality and supervision simultaneously significantly influence employee performance at the Lahat Regency Communication and Information Service.